-6g+20=-10g

Simple and best practice solution for -6g+20=-10g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6g+20=-10g equation:


Simplifying
-6g + 20 = -10g

Reorder the terms:
20 + -6g = -10g

Solving
20 + -6g = -10g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '10g' to each side of the equation.
20 + -6g + 10g = -10g + 10g

Combine like terms: -6g + 10g = 4g
20 + 4g = -10g + 10g

Combine like terms: -10g + 10g = 0
20 + 4g = 0

Add '-20' to each side of the equation.
20 + -20 + 4g = 0 + -20

Combine like terms: 20 + -20 = 0
0 + 4g = 0 + -20
4g = 0 + -20

Combine like terms: 0 + -20 = -20
4g = -20

Divide each side by '4'.
g = -5

Simplifying
g = -5

See similar equations:

| 43=-9-14x | | 12x+5=149 | | 10y-8y-y=0 | | x^2+8x=2x^2-40 | | .4x+4=40 | | 20-8=x/3 | | 1800+450=600p+1200 | | 5(x+4)+2=5x+2 | | (x^2-4x+16)(x+4)=0 | | 43=-9-14r | | 25x+16=40x | | 38.72+23.19+n=31.18 | | 22x-6-16x+4=18x-8-12x+15 | | 5y-26=-6(y+8) | | -2-10y+11y=-4 | | 17=-1-9a | | 4-0.7(p-3)=0.2(4p-3) | | 15+4x=5x+5 | | -9+x=.875x-23 | | -4x-4x=46-6 | | X^2+8x=2x^2+2x-40 | | X^12=9 | | yx+6x=7 | | 3/x^3-27 | | 12s-5-11s=-3+3 | | -9d-19=-11d+19 | | x^2+y^2-6x-16y+57=0 | | yx+6y=7 | | 300+20x=500+12y | | 16-0.3(m-13)=0.4(5m-13) | | r^2-20rs-44s^2=0 | | 4(2x-1)=-100 |

Equations solver categories